Artikel Pengelolaan Media Pembelajaran Sekolah Dasar - Eny Munisah (Edukasi Lingua Sastra, 2020)
Management of learning media is a part of efforts to improve the quality of education. As for the indicators that must be considered in the management of learning media especially: planning instructional media, organizing media, learning media management, evaluating media of the school, it is expected that the preparation of media programs can run effectively with the learning programs that have been made so that it can contribute positively to learning. The learning media management process must go hand in hand with school programs, it is necessary to manage a management of learning media in elementary school that is responsible for administering all activities related to learning media management, understanding of media management is important for the officer in planning media programs, classification of media, the grouping of media based on the condition of each school or based on certain subjects so that the media can be used optimally in the classroom or in out door class. Supervision should be carried out programmatically by the school principal and personnel at the relevant agencies of the district and district level offices are expected to be input of increasing the development of learning media management n the next year.